ENHANCING STUDENT-CENTERED LEARNING AND 4C SKILLS THROUGH PADLET IN A RESTRICTED GADGET ISLAMIC BOARDING SCHOOL - Taufiq, Wahyu; Novita, Dian; Dilna, Sema Guine; Nurbatra, Laila Hikmah (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2026)
This study investigates the use of Padlet as a digital collaborative tool to support student-centered English learning in a restricted gadget environment. The study was conducted at an Islamic girls’ boarding school in Malang, East Java, Indonesia. It involved 23 seventh-grade female students who were studying the topic of Indonesian flora and fauna. A convergent mixed-methods design was employed, with data collected through a student perception questionnaire, semi-structured interviews, and handwritten reflection sheets. Findings showed that Padlet significantly increased student motivation, participation, and confidence in sharing idea in English. The platform also enhanced 4C skills, especially communication and collaboration. The combination of Padlet activities with handwritten reflection tasks effectively encouraged originality and reduced copy-paste habits. Even under strict prohibition of personal mobile phones, Padlet implemented via the school computer laboratory proved practical and effective. This study concludes that a balanced integration of digital collaboration and non-digital reflection offers a promising model for technology-enhanced learning in Islamic boarding schools.